2013
DOI: 10.2139/ssrn.2328136
|View full text |Cite
|
Sign up to set email alerts
|

Novartis v Union of India and the Person Skilled in the Art: A Missed Opportunity

Abstract: Abstract:The Indian Supreme Court's (SC) decision in Novartis v Union of India (UOI), decided earlier this year, formalizes a concerted and focused attempt by Indian law-makers to reject trivial secondary pharmaceutical inventions. The SC concluded that S 3(d) of the Indian Patents Act made new forms of known substances ineligible for patents in the absence of 'enhanced efficacy', which in this case was defined as 'therapeutic efficacy'. This paper argues that the SC wrongly ignored the context of S 3 and Chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…50 The idea that patent laws can, or should be, tempered so as to inhibit the adverse impact they have on monopoly pricing or access to protected medicines has led to some loosening or questioning of legal standards in domestic laws (for instance the compulsory licensing standards in Canada and Thailand, 51 or the Indian Supreme Court's observation on prices in Novartis v Union of India). 52 There have been calls for a mechanism over and above the so-called TRIPS flexibilities that would subject international trade agreements to review standards to protect and advance human rights 53 . However, many of these interventions remain sporadic and anecdotal -partial wins that are not seen as easily replicable or enforceable in the law minus political will.…”
Section: Patents Human Rights and Access To Patented Medecinesmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The idea that patent laws can, or should be, tempered so as to inhibit the adverse impact they have on monopoly pricing or access to protected medicines has led to some loosening or questioning of legal standards in domestic laws (for instance the compulsory licensing standards in Canada and Thailand, 51 or the Indian Supreme Court's observation on prices in Novartis v Union of India). 52 There have been calls for a mechanism over and above the so-called TRIPS flexibilities that would subject international trade agreements to review standards to protect and advance human rights 53 . However, many of these interventions remain sporadic and anecdotal -partial wins that are not seen as easily replicable or enforceable in the law minus political will.…”
Section: Patents Human Rights and Access To Patented Medecinesmentioning
confidence: 99%
“…It does so by denying patents to new forms of known pharmaceuticals, which prevents an extended monopoly on an already patented pharmaceutical. 126 Rather surprisingly, however, Shadlen and Sampat, 127 conducting the first systematic study of patents on secondary inventions in India, Brazil and Argentina, found that measures designed to inhibit secondary inventions are having little effect. There could be a number of reasons for this, including the competence of patent examiners and their learning needs, 128 as well as the presence of technical or legitimacy networks that may be working to undermine the real effect of the provisions.…”
Section: The Technocratic Patent System and The Difficulty In Accomodmentioning
confidence: 99%
“…Quite how the EPO came to interpret these words as allowing patents for particular uses of patentable pharmaceutical products is unclear. Setting aside this conundrum about patents for first medical uses of patented compounds, Thambisetty indicates that "as a response to pressure from the pharmaceutical industry the EPO was interested in extending patent product protection to second medical use of known products" (Thambisetty 2009: 17, emphasis added). She provides an example of the minor variation in wording designed by the Swiss Patent Office to overcome this exclusion (a technique known as "Swiss medical claims").…”
Section: 5c Strategic Games Playing: Semanticsmentioning
confidence: 99%
“…Formal statements from patent offices suggest they do not see consumers or non-patenting innovators among their "stakeholders". Several well-informed students of the patent system suggest that patent offices have become part of an in-grown self-reinforcing community impervious to (and generally unaware of) the evidence as to possible negative impacts from the current "strong" 46 system (Thambisetty 2009;Drahos 2010). 47 To offset these continuing pressures patent systems need clear built-in systems for effective oversight, including audit and evaluation, and mechanisms to draw them into wider policy circles.…”
Section: Transparency Evaluation and Auditmentioning
confidence: 99%